Control of Dysmicoccus brevipes (Hemiptera: Pseudococcidae) on the pineapple fruit, San Carlos, Costa Rica. - Vindas, Alexandra Miranda (2013)
The study evaluated 6 products for Dysmicoccus brevipes control in pineapple production (Ananas comosus). The laboratory test was conducted in the BioEco Natural Company S.A., biocontrol laboratory in Aguas Zarcas, San Carlos, while the field trials were conducted in a commercial pineapple plantation in Venecia, San Carlos. In the laboratory test Beauveria bassiana (4.0 x 1010 spores.g-1); Metarhizium anisopliae (1.0 x 1010 spores.g-1); a mixture of both fungi (0.5 g + 0.5 g.l-1 of 4.0 x 1010 spores.g-1 + 1.0 x 1010 spores.g-1 distilled water); a potassium salt liquid soap “Goyca®” (7 ml.l-1); the botanical extract (Biorep®) (a hot pepper, garlic, onion, mustard and gavilana mixture) (7 ml.l- 1); and distilled water as control, were evaluated. The most promising results were with the botanical extract and the liquid soap, which caused faster mortality. The treatments evaluated in the pineapple plantation, var. MD-2, were the same, except for the control where products in use in the commercial farm were used: Diazinon® 60 EC (diazinon) (0.5 ml.l-1) and Sevin® 80 WP (carbaril) (1 kg.ha-1). The botanical extract resulted in the lowest incidence of mealybugs (X=6.4), < control (X=10.8), < the Goyca (X=13.7), < M. anisopliae (X=44.4), < B.bassiana (X=45.1), and < B.b+M.a (X=45.8). There were no differences in fruit length and girth as a result of the applied products. The cost per hectare was similar among treatments, being lowest in the control (18.800 colons), and highest in the botanical extract (29.700 colons). The results show as best option the use of the liquid soap used to control D. brevipes.